The effect of deterrence policy in software piracy: cross-cultural analysis between Korea and Vietnam. (November 2014) - Yoo, Chul-Woo; Sanders, G Lawrence; Rhee, Cheul; Choe, Young-Chan
This research focuses on the comparison of piracy behaviour between Korea and Vietnam, and empirical validation of a model of software piracy based on expected utility theory, deterrence theory and institution isomorphism theory. A survey of 132 (Korea) and 145 (Vietnam) respondents was carried out in 2008 and PLS (Partial Least Square) was utilized for the analysis. Our results indicate that the relationships between punishment certainty and attitude, and mimetic pressure and intention, are significantly different between Korea and Vietnam. Several implications are considered from the political and cultural aspects.